Effect of Lactobacillus Probiotic Strains on Microbiological Spectrum of Artemia Nauplii - Khudyi, Oleksii; Lazarenko, Liudmyla; Karucheru, Oksana; Babenko, Lidiya; Khuda, Lidiia; Dzhuravets, Yuliia; Spivak, Mykola (Чернівецький національний університет імені Юрія Федьковича, 2021)
This study investigated the possibility of bioencapsulation of three probiotic strains of lactic acid bacteria Lactobacillus casei ІМВ В-7280, L. acidophilus ІМВ В-7279 and L. delbrueckii subsp. bulgaricus ІМВ В-7281 into Artemia nauplii and the influence of bioencapsulation duration on live feed microbiota and mortality. Examined LAB strains colonize Artemia nauplii differently. The highest rate of colonization was observed after applying L. delbrueckii, the lowest - L. acidophilus. Results of microbiological study showed that intact nauplii of control groups were contaminated by fish pathogens such as Pseudomonas spp., Enterobacteriaceae spp., Staphylococcus spp., Streptococcus spp. and microscopical fungi Candida spp.. The results of the study determined that all three probiotic strains positively affected nauplii microbiological spectrum. In particular, application of L. casei and L. delbrueckii decreased the amount of all bacteria determined for control groups, Candida spp. were eliminated. L. casei had that effect regardless of procedure duration. Application of L. acidophilus led to Staphylococcus spp. and Pseudomonas spp. suppression on 12th hour of enrichment. Despite the fact that L. delbrueckii colonizes nauplii more effectively, L. casei suppresses pathogens more effectively. Artemia enrichment with all three strains of LAB allows to reduce the mortality rate 5 times within 12 hours of exposure. This effect may be beneficial for supporting viability of fed organisms in automatic feeders during fingerlings rearing.
Мікробіологічний спектр науплій артемії за дії пробіотичних штамів молочнокислих бактерій роду Lactobacillus
biochemistry and bitechnology
Keywords: Artemia; probiotics; bioencapsulation; mortality; microflora